The new look of behavioral genetics in developmental psychopathology gene-environment interplay in antisocial behaviors. [article]. - Moffitt, T. E.
This article reviews behavioral-genetic research to show how it can help address questions of causation in developmental psychopathology. The article focuses on studies of antisocial behavior, because these have been leading the way in investigating environmental as well as genetic influences on psychopathology. First, the article illustrates how behavioral-genetic methods are being newly applied to detect the best candidates for genuine environmental causes among the many risk factors for antisocial behavior. Second, the article examines findings of interaction between genes and environments (G x E) associated with antisocial behavior, outlining steps for testing hypotheses of measured G x E. Third, the article envisages future work on gene-environment interplay, arguing that it is an interesting and profitable way forward for psychopathology research. -- (from the author)